On the interaction between own revenues and intergovernmental transfers: evidence from Argentinean local governments - Porto, Alberto (2021)
We study the interaction between intergovernmental transfers on the level and the structure of local own revenues. Based on a sample for Argentina’s local governments, findings indicate that transfers facilitate local revenues collection. This effect is more pronounced in urban local governments, with higher population density, poverty, and demand for public services. In addition, transfers bias own revenues composition. That is, higher transfers lead to higher local tax collection, which is obtained through less distortionary taxation (i.e., property tax). Interestingly, this bias is stronger for local governments with a higher share of divisible public goods (that are likely to be financed according to the "benefit principle”). Results are robust to a battery of different estimation methods and can be rationalized with theory from public finance and political economy as well. As a whole findings might have important policy implications on local governments’ public finance.